The influence of community characteristics towards telecentres success - Yusop, Nor Iadah; Mohd Yusof, Shafiz Affendi; Mat Aji, Zahurin; Ibrahim, Huda; Kasiran, Mohd Khairudin; Md Dahalin, Zulkhairi; Abdul Ghani, Nor Farzana; Abd Razak, Rafidah; Hassan, Syahida; Rahmat, Abdul Razak (Canadian Center of Science and Education, 2010)
Telecentres are physical spaces that provide public access to information and communication technology particularly the Internet for educational, personal, social, and economic development. This paper will closely look into the characteristics of the community that influence the success of telecentres. Although there are a number of influential factors in regards to community characteristics, the emphasis will be on groups and networks factor. Survey was conducted to collect data from users regarding their use of telecentres. In the questionnaire, apart from the users’ profiles, items related to the groups and networks were also included.Sampling was done based on a population comprising of telecentres implemented by state governments, non-governmental organizations, and private sectors. The findings suggest that there are some indications showing certain self belonging, as consequences to the usages of telecentres, to a group and establishing networks which can contribute to the success of telecentres.